Organizational Silence in Educational Leadership Practice - Pierre Marcello Lopulalan (Education Achievement: Journal of Science and Research, 2026)
Organizational silence is a phenomenon that has the potential to hinder the effectiveness of educational leadership, especially in complex urban school environments. This study aims to analyze the form, causative factors, and impact of organizational silence in public high schools in South Tangerang City and West Jakarta. The research uses a qualitative approach with a case study design through in-depth interviews, observations, and document analysis. The data was analyzed thematically. The results of the study show that organizational silence is reflected in low teacher participation in decision-making, dominance of top-down communication, and reluctance to convey criticism. Key factors include hierarchical organizational culture, performance pressures, concerns about professional risks, and weak psychological safety. This condition has an impact on the inhibition of innovation, the low quality of decisions, and the lack of involvement of educators. This research emphasizes the importance of transformational leadership that encourages open and participatory communication to create an adaptive organizational environment in the context of urban education.